“Doomed to be excluded”: the questions of ethnic education, citizenship and ethnic identity (Journal of history, 2023)
This article provides an overview of ethnic identity theory, ethnic education, and citizenship as exemplified by ethnic Koreans in Japan. The ethnic education of Koreans in Japan is related to the North Korean school system. Therefore, the choice of education was conditioned by the choice of political trajectory and individual orientation of ethnic Koreans. The authors suggest that the choice of ethnic education in the Japanese context leads to inevitable social exclusion in ethnic Korean children. The authors examine the effects of ethnic school education in Japan. Through unstructured interviews, the authors gathered arguments to support the theory of ethnic discrimination in education. First, ethnic Koreans can make choices in education. Secondly, the direction of education carries not only an ethnic characteristic but also a political one. By choosing a Korean school, young Koreans are choosing a commitment to the North Korean regime and ideology. Thirdly, young people inevitably face stigmatization and discrimination against their ethnicity when choosing a Korean education. The authors determined that segmented assimilation, in which ethnic identity shapes educational trajectories, works differently. In the case of Koreans in Japan, the reverse causal order works: educational experiences shape ethnic identity.Keywords: Koreans, Japan, ethnic identity, ethnic education, citizenship, assimilation